Cisto esplênico não-parasitário e não-neoplásico - Alvarez,Glauco da Costa (1998)
The authors present a rare case of pathology from spleen, a nonparasitic, non-neoplastic splenic cyst, in an adult male patient without a previous history of abdominal trauma. Principal clinical findings were pain in left upper quadrant, nausea, regurgitation and precocious satiation. On investigation, ultrasonography and CT scan showed an expansive lesion in the spleen, compressing the stomach. Surgical procedure was splenectomy and a microscopical examination revealed a non- parasitic, non-neoplastic splenic cyst. Splenic cysts are usually benigns, but surgical remotion is necessary when they are symptomatic or exist risk of rupture. In this report is presented the classification of splenic cysts, clinical manifestations, diagnostics methods and discussed their surgical treatment.